Migration society? Critical Perspectives of Migration, Capitalism and Arrival - Kaloianov, Radostin (Momentum Quarterly, 2021)
The article argues for a comprehensive change of perspective, based on the concept of the ’migration society’ and the attempt to critically question the concept of migration beyond conventional definitions of migration as wandering. This change of perspective originates in the critique of the idealization of migration as wandering and the shift in conceptional focus from the wandering to the arrival and settling-down of migrants. This paradigm change does not limit itself to the topic of migratory mobility and extends to the analysis of migrant arrival. The wandering-centered scenarios of migrant arrival, such as those of integration and diversity management, are contrasted with new critical understandings of what migrant settlement is all about. Setting the focus on migrant arrival, this approach shows ambivalences, contradictions, and polarizations, that characterize migrant new arrivals as arrivals from below. The point of departure to critically construe migrant settling-down is to take this process literally as a setting a foot down allowing, a settling at the bottom rungs of the social ladder. What migration society is and what is going on in migration society is summed up by the formula: It’s all about arriving!